Análises biológicas e molecular de linhagens de Trichogramma pretiosum (Hymenoptera: Trichogrammatidae) coletadas no Estado do Ceará - Coutinho, Cristiane Ramos (2018)
The study of species / lineages of local parasitoids is an essential item for the implementation of biological control programs, since they are adapted to the habitats in which they will be released. The objective of this study was to determine the biological parameters of two Trichogramma pretiosum Riley (Hymenoptera: Trichogrammatidae) lineages collected in the rural areas of Ubajara and Guaraciaba do Norte, municipalities in the region of Serra da Ibiapaba, Ceará State, in order to guarantee the quality of the progeny and establish the first parameters to allow the use in biological control. The majority of experiments were carried out at the Laboratory of Applied Entomology (LEA) of the Federal University of Ceará (UFC), Fortaleza, Ceará, Brazil. The biological parameters of the Ubajara (1) and Guaraciaba (2) lineages were evaluated by alternating the number of females of the parasitoid (1, 3, 6 or 9 females) and the density (10, 20, 30, 40 or 50) of Anagasta kuehniella Zeller (Lepidoptera: Pyralidae), Neoleucinodes elegantalis Guinée (Lepidoptera: Crambidae) and Spodoptera frugiperda J E Smith (Lepidoptera: Noctuidae). Using the best densities, it was also evaluated the performance of the two lineages in the hosts at times of exposure to parasitism (6, 12, 24 and 48 hours). It was also determined the temperature of impact (15, 20, 25, 30 and 35°C) in the lineages biology, thus determining the thermal requirements of parasitoids on N. elegantalis eggs. The experiments were installed in a completely randomized experimental design with 12 replicates. The best density was determined by the first derivative of the paraboloid regression of percentage of parasitism and emergency data. The other parameters: sexual ratio; number of parasitoids emerged per egg; females and males longevity and cycle duration (egg-adult) were submitted to ANOVA and the means compared by Duncan's test (p ≤0.05). The thermal requirements were obtained using the hyperbola method. One of the experiments was carried out at the Laboratory of Entomology of the University of California (UCR), Riverside, California, USA, in which it was tried to detect natural infections of Wolbachia in the lineages of Trichogramma. DNA extractions and polymerase chain reaction (PCR) were carried out using primers ITS-2 and 16s. The highest rates of parasitism were observed for lineage 2 in all hosts. The densities of 7,3 females/26,4 eggs of A. kuehniella, 3,3 females / 40,1 eggs of N. elegantalis and 4,5 females / 10,8 eggs of S. frugiperda provided higher emergence rates for lineage 2. The parasitoid / host densities of 6:10 and 3:10 A. kuehniella, 6:20 and 6:10 N. elegantalis, 9:50 and 9:20 S. frugiperda in the Ubajara and Guaraciaba lineages, respectively, presented favorable results in the which refers to the reproduction of the local lineages. Lineages 1 and 2 showed similar potential at the different exposure times studied and the temperature altered the biological parameters, with the cycle duration of lineages 1 and 2 decreasing with the increase of the same. Molecular analysis did not detect presence of Wolbachia in the local lineages. The main biological parameters of the lineages were determined to be satisfactory, thus confirming that one of the first steps aimed at the use of the lineages in biological control programs was successfully obtained.